Design, implementation, and evaluation of a shared LoRa network application architecture. (29th July 2021) - Peng, I-Hsuan; Tai, Yu-Chun; Lee, Pei-Chun
This research proposes an internet of things application architecture based on the essence of 'sharing and reciprocity' - a shared LoRa network application architecture. To prove the feasibility of this architecture, we designed and implemented a pet tracking system which consists of the LoRa tracking motes, the fixed and portable shared LoRa gateways, a service mobile app, and the back-end service, exploiting technologies such as LoRa, Global Positioning System, Bluetooth Low Energy, Arduino UNO microcontroller, mobile app, and RESTful API. Moreover, this research evaluates the performance of the shared LoRa network and the electricity consumption of the LoRa tracking mote as well as the portable shared LoRa gateway. We confirm that the portable shared LoRa gateways do improve the overall network performance, and the users do not need to worry about the battery life of the devices in everyday life situations.